KONSEP SYURA DALAM AL-QUR???AN (ANALISIS SEMIOTIKA ROLAND BARTHES) - Nafisah Innayati; Fikru Jayyid Husain (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2023)
Abstract This paper discusses the concept of shura or deliberation in the Qur'an. In the contemporary era, shura is often associated with several modern political theories, such as the democratic system. That will reduce the meaning of shura and democracy. This paper will discuss whether the concept of shura, as a state institution and institution in modern times, can be integrated with a democratic system. To answer these problems, the writer uses a linguistic approach as a tool for analysis, that is semiotics approach. The term shura is a symbol or sign of conveying a message that must be interpreted. One of the semiotic theories is the approach offered by Roland Barthes. There are two stages in Barthes' semiotic theory. The first stage is the linguistic system or denotative meaning and the second stage is the mythological system or connotative meaning. The results obtained from this study are: first, in the linguistic system or denotation meaning of the word shura/deliberation has the meaning of taking opinions (opinions), negotiations, and deliberations that aim to reach a joint decision. Second, the mythological system or connotative meaning, the word shura/deliberation in this system is often referred to as democracy because the two concepts have something in common, namely to realize a government based on justice in accordance with joint decisions. However, equating the two terms as one unit in the sense of synonymity is not the right thing, because in addition to having similarities, shura and democracy also have very significant differences.